Modified Steam-Turbine Rankine Cycle without Rejection of the Cycle Condensation Heat, Driven by a Wet-Vapor-Region Thermocompressor - Branko Stanković (Energija, Ekonomija, Ekologija)
The disclosed concept relates to a novel modified and simplified steam-turbine Rankine cycle without rejection of the cycle waste heat of condensation, which is driven by a thermocompressor (ejector) operating in the wet-vapor region. The thus modified steam-turbine Rankine cycle can theoretically achieve the maximum possible thermal efficiency (~100%). The wet-vapor mixture circulating within the thermocompressor is being separated in a dedicated cylindrical separation tank, so that the saturated water is pumped to a water heater where it receives the cycle heat input, while the saturated vapor is expanded in a backpressure steam turbine producing useful mechanical work and is then recirculated back to the thermocompressor, where it is being re-pressurized by means of the primary fluid (pumped and heated saturated water). The concept can be applied to steam-turbine-cycle power-plants fueled by: coal or solid/liquid/gaseous fuel, waste heat, nuclear fuel (used by boiling water reactors, pressurized water reactors, pressurized heavy-water reactors, gas-cooled reactors, molten salt reactors or liquid-metal-cooled fast reactors) or renewable energy sources (Solar energy, biomass, geothermal). The concept can also be applied as the “bottoming” steam-turbine-cycle part of a combined gas-turbine/steam-turbine cycle power plant.